Effect of peribulbar block on emergence agitation in children undergoing strabismus surgery under desflurane anaesthesia. (3rd September 2018) - Makkar, Jeetinder Kaur; Kuberan, Aswini; Singh, Preet Mohinder; Gopinath, Arun Magadi; Jain, Kajal; Singh, Jaspreet; Singh, Narinder Pal
Abstract : Background: Strabismus surgery in children may be associated with a high incidence of emergence agitation that may be related to pain and visual disturbances. The objective was to evaluate the effect of peribulbar block on the incidence of emergence agitation in children undergoing strabismus surgery under desflurane anaesthesia. Methods: Fifty-six healthy children aged 2–10 years, undergoing strabismus surgery under general anaesthesia, were recruited. Children were randomly allocated to receive fentanyl 2 µg/kg (Group F) or peribulbar block (Group PB) with 0.3 ml/kg of 0.25% bupivacaine + 2% lignocaine. The primary outcome of the study was incidence of emergence agitation; secondary outcome measures were time to first rescue analgesia, the incidence of oculocardiac reflex and vomiting. Results: Of 52 children, 14/25 (56%) children in Group F developed emergence agitation compared with 3/27 (11.11%) in group PB ( p = 0.001). Postoperatively, the paediatric anaesthesia emergence delirium scores showed significantly lower emergence agitation in the PB group with a median (IQR) of 0.00 (0.00–2.00) compared with group F (5.5 (0.75–8.75) at all time intervals ( p = 0.003 Mann–Whitney test). Pain scores were comparable between groups (group F 48% vs. group PB 25.9%). The time to first rescue analgesia was increased in group PB (126.875 ± 38.22 min vs. 88.08 ± 28.48 min in group F). The oculocardiac reflex occurred in 7/25 in Group F compared with 1/27 in Group PB ( p = 0.015). There was no difference in the incidence of postoperative vomiting (24% in Group F vs. 22% in Group PB). Conclusion: Use of peribulbar block in children undergoing strabismus surgery under desflurane anaesthesia was associated with reduced incidence of emergence agitation and oculocardiac reflex but did not significantly increase the time to first analgesic or the incidence of pain and vomiting. A sub-tenon block may be safer and provide better operating conditions and equal analgesia.